Temporal distribution of peak running demands relative to match minutes in elite football - Bradley Thoseby; Andrew Govus; Anthea Clarke; Kane Middleton; Ben Dascombe (Termedia Publishing House, 2021)
The peak match running demands of football (soccer) have been quantified across time durations of 1-10 min, however, little is known as to when the peak match running demands occur within match play. Data were collected from 44 elite footballers, across 68 fixtures (Files = 413, mean ± SD; 11 ± 8 observations per player, range; 1-33), with peak match running demands quantified for each playing half at ten incremental rolling average durations (1 min rolling averages, 2 min rolling averages, etc.). Data were assessed if players completed the full match. Three measures of running performance were assessed total distance (TD), high-speed distance (> 19.8 km·h-1) (HSD) and average acceleration (AveAcc)], with the in-game commencement time of the peak running demands recorded. Descriptive statistics and normality were calculated for each rolling average duration, with the self-containment of shorter rolling average epochs within longer epochs also assessed (e.g. Do the 1 min peak running demands occur within the 10 min peak running demands). Peak TD and AveAcc demands occurred early in each half (median time = 7-17 min and 6-16 min, respectively). Conversely, peak HSD covered was uniformly distributed (Skewness = 0-0.5, Kurtosis = 1.7-2.0). There were low-moderate levels of self-containment for each peak match running period (10-51%), dependent upon metric. Peak match running demands for TD and AveAcc occurred at similar stages of a match where TD and acceleration volumes are typically greatest, whereas peak HSD demands appeared more unpredictable. These timings may help inform training prescriptions in preparation of athletes for competition.